Transcriptomic Analysis of Zebrafish TDP-43 Transgenic Lines - Lissouba, Alexandra; Liao, Meijiang; Kabashi, Edor; Drapeau, Pierre (Frontiers in Molecular Neuroscience, 2018)
Amyotrophic lateral sclerosis (ALS) is a late-onset progressive neurodegenerative disorder that affects both upper and lower motor neurons, leading to muscle atrophy with spasticity and eventual death in 3 to 5 years after the disease onset. More than 50 mutations linked to ALS have been found in the gene TARDBP, encoding the protein TDP-43 that is the predominant component of neuronal inclusions in ALS. TDP-43 is an RNA binding protein with glycine-rich domains that binds to more than 6,000 RNAs in the human brain. However, ALS-related mutations do not appear to affect the function of these genes, indicating that a toxic gain-of-function may occur. We generated transgenic zebrafish lines expressing human TDP-43, either the wild-type form or the ALS-causative G348C mutation identified in a subset of ALS patients, with the transgene expression driven by an inducible heat shock promoter in order to bypass a potential early mortality. The expression of the mutant but not the wild-type human TDP-43 in zebrafish embryos induced a reduction of the locomotor activity in response to touch compared to controls and moderate axonopathy of the motor neurons of the spinal cord, with premature branching of the main axonal branch, recapitulating previous results obtained by mRNA injections. We used these lines to investigate transcriptomic changes due to the presence of mutant TDP-43 using RNA sequencing and have found 159 genes that are differentially expressed compared to control, with 67 genes up-regulated and 94 genes down-regulated. These transcriptomic changes are in line with recent transcriptomic data obtained in mice models, indicating that these zebrafish transgenic lines are adequate to further study TDP-43-related ALS.